Seeing double : intercultural poetics in Ptolemaic Alexandria - Stephens, Susan A. (Joan Palevsky imprint in classical literature., 2003)
When, in the third century B.C.E., the Ptolemies became rulers in Egypt, they found themselves not only kings of a Greek population but also pharaohs for the Egyptian people. Offering a new and expanded understanding of Alexandrian poetry, Susan Stephens.